Nano calcium carbonate special for acrylate adhesive and preparation method of nano calcium carbonate

By modifying the surface of nano calcium carbonate, the problems of poor fluidity and weak binding force in acrylate adhesives are solved, the dispersion performance and moisture-heat aging resistance are improved, the service life of the adhesive is extended and the adhesion is enhanced and Durability.

CN119307194APending Publication Date: 2025-01-14GUANGXI HUANA NEW MATERIALS TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411663003.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Nano calcium carbonate in acrylate adhesives has poor fluidity and weak binding force due to its high surface energy, hydrophilic and strong polar properties, resulting in poor fluidity and weak binding force in processing, resulting in a decline in material performance.

Method used

The carbonization reaction was carried out by diluting lime emulsion and carbon dioxide was introduced. Then the surface modification was performed using a composite of polyoxyethylene glycerol triricinate, nonylphenol polyoxyethylene ether sulfate and sodium stearate. Propyltriethoxysilane isocyanate is subjected to secondary surface modification to form a solid interfacial layer to improve dispersion and stability.

Benefits of technology

It significantly improves the dispersion performance of nano calcium carbonate in acrylate adhesives and resists moisture and heat aging, extends the service life of the adhesive, and enhances adhesion and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143925370000121
    Figure BDA0005143925370000121
  • Figure BDA0005143925370000131
    Figure BDA0005143925370000131
  • Figure BDA0005143925370000132
    Figure BDA0005143925370000132
Patent Text Reader

Abstract

The invention discloses a preparation method of special nano calcium carbonate for an acrylate adhesive, which comprises the following steps: S1, diluting lime milk to obtain lime milk raw slurry, introducing mixed gas containing carbon dioxide under a stirring condition to carry out carbonation reaction, stopping introducing gas after the reaction is finished, and aging to obtain calcium carbonate suspension; s2, carrying out surface modification treatment on the nano calcium carbonate suspension by using a compound of polyoxyethylene glycerol triricinoleate, nonylphenol polyoxyethylene ether sulfate and sodium stearate; s3, carrying out ultrasonic treatment on the nano calcium carbonate suspension subjected to primary modification, adding isocyanate propyl triethoxy silane, and carrying out secondary surface modification treatment; and S4, carrying out filter pressing, drying, crushing and sieving on the modified nano calcium carbonate slurry to obtain the modified nano calcium carbonate. According to the prepared nano calcium carbonate filled acrylate adhesive, the damp-heat aging resistance and thixotropy of the nano calcium carbonate filled acrylate adhesive can be improved, and the adhesiveness, durability, stability and the like of the acrylate adhesive are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of calcium carbonate preparation, and in particular to nano calcium carbonate special for acrylic adhesive and a preparation method thereof. Background Art

[0002] Acrylate adhesive is a two-component adhesive based on free radical graft copolymerization of (meth)acrylate. The ester group in the acrylate structure has strong hydrogen bonding, so it is widely used as an adhesive and has the characteristics of rapid room temperature curing, high strength, good toughness, oil surface bonding, strong adaptability, and easy use. Acrylate adhesives are widely used in the manufacture of aviation and aerospace equipment, in the manufacture of automobiles, ships, electrical appliances, instruments, and the decoration, renovation, and maintenance of buildings, the manufacture of medical equipment, and the maintenance of daily furniture in the structural bonding, small parts assembly, large parts assembly, emergency repair, anti-seepage and leak plugging, nameplate pasting, etc.

[0003] Filler modification of various adhesives is a common and effective modification method. The volume of the adhesive can be increased by adding fillers, thereby reducing the cost. At the same time, the addition of fillers can also improve the poor heat resistance of the adhesive itself, high curing shrinkage, low hardness and unstable viscosity. As an important filler for adhesives, nano calcium carbonate is not only low in price, but can be used for incremental filling to reduce the cost of acrylic adhesives. It also has good compatibility with adhesives, can accelerate the cross-linking process of adhesives, improve thixotropy, and improve adhesion, tensile strength and reinforcement effects. However, the surface of nano calcium carbonate shows hydrophilic and polar properties, easily absorbs water, and has poor compatibility with polymers. It is difficult for the two to form a stable bond at the interface. Direct or large-scale filling may reduce certain mechanical properties of the material. By changing the original properties of the surface of nano calcium carbonate, such as lipophilicity, oil absorption rate, wettability, and mixture viscosity, the affinity, compatibility, processing fluidity and dispersibility of nano calcium carbonate and polymers can be improved, and the bonding force between the filler and the polymer interface can be enhanced, so that the comprehensive performance of the composite material can be significantly improved. Therefore, the surface properties of nano-calcium carbonate determine its application effect in different application systems.

[0004] Chinese patent CN106243780A discloses an aging-resistant composite calcium carbonate and a preparation method thereof. The invention combines calcium carbonate with materials with good comprehensive properties such as epoxy resin, polyurethane resin, nano-magnesium oxide, amino resin, etc., improves the production process, and uses modifiers to effectively increase the aging resistance of the composition. The invention also has a short production cycle, stable quality, low cost, and high application value.

[0005] Chinese patent CN113930166A discloses a high-hardness acrylic adhesive. The patent uses nano calcium carbonate as an inorganic filler to prepare an acrylic adhesive, the cured product has a smooth surface without pores and low shrinkage, the cured product hardness (Shore D strength) is greater than 75, the problems of bubble generation and yellowing can be effectively improved, and the tensile shear strength can reach the substrate destruction.

[0006] Chinese patent CN113025215A discloses a structural adhesive for automobiles and a preparation method thereof. Adding 10-20 parts of an inorganic filler into the system, wherein the filler is one of calcium carbonate powder, silicon dioxide powder, talcum powder and titanium dioxide, can significantly improve the viscosity and specific gravity at 25°C, and the adhesive has good stability.

[0007] Chinese patent CN115029094A discloses a room temperature curing two-component acrylic adhesive, which uses calcium carbonate, silicon dioxide and the like as inorganic fillers to prepare a room temperature curing two-component acrylic adhesive, which significantly improves the tensile shear strength, curing speed and softness of the spline.

[0008] Chinese patent CN103305131B uses fumed silica, calcium carbonate and nano-alumina as inorganic fillers to prepare highly weather-resistant acrylic structural adhesives, which effectively solves the defects and shortcomings of acrylic structural adhesives in the prior art, such as long positioning time, long complete curing time, and poor resistance to moisture and heat aging.

[0009] Gao Yanmin et al. added nano calcium carbonate to ethanol and ultrasonically dispersed it for 2 hours, then added the prepared DL-α-alanine aqueous solution, controlled the pH value and temperature of the solution, and after a period of reaction, took out the solution for suction filtration, washing and drying to obtain modified nano calcium carbonate. The modified nano calcium carbonate prepared by this method can effectively improve the bonding performance of the adhesive, has good dispersibility in the adhesive, and the agglomeration phenomenon can be significantly improved. (Gao Yanmin, Yuan Qingfeng, Zhu Jingyan, et al. Effect of surface grafting modification of nano calcium carbonate on the performance of epoxy adhesives [J]. Journal of Jiangsu University of Science and Technology (Natural Science Edition), 2009, 23(03): 213-216)

[0010] Chinese patent CN105778568A discloses a surface treatment method for nano calcium carbonate for photovoltaic adhesive, comprising the following steps: adding nano calcium carbonate slurry into a reaction kettle, stirring, and heating to 60-90°C; adding a saponified compound surface treatment agent of stearic acid and polyoxyethylene stearate to the slurry for surface treatment, stirring for 20-30 minutes, and obtaining modified nano calcium carbonate; then dehydrating by filter pressing, and drying by a chain belt dryer at a drying temperature of 110-135°C; and then crushing, grading, and packaging the dried material according to conventional methods to obtain a nano calcium carbonate product.

[0011] Chinese patent CN106752984A discloses a method for preparing an acrylic adhesive for bonding automobile skirtings. The patent uses calcium carbonate as the main filler, which can reduce the thixotropy of the product, make it easy to scrape and apply, and have good heat and moisture resistance; in combination with other ingredients, it can effectively reduce the exothermic temperature of the product (the exothermic peak is reduced from 115 degrees to below 80 degrees), making the curing more stable, the volume shrinkage rate is less than 1%, and the curing time is short, which can shorten the construction period.

[0012] Chinese patent CN103305131B uses fumed silica, calcium carbonate, and nano-alumina as inorganic fillers to prepare highly weather-resistant acrylic structural adhesives, which effectively solves the defects and shortcomings of acrylic structural adhesives in the prior art, such as long positioning time, long complete curing time, and poor resistance to moisture and heat aging.

[0013] Liu Shudi added stearic acid to anhydrous ethanol and stirred at 50°C for 15 min, then added a water-ethanol mixed solution (V 水 :V 乙醇 =3:1) in a nano calcium carbonate slurry, stirred at a constant temperature for 2 hours to obtain modified nano calcium carbonate. The obtained nano calcium carbonate is filled into the acrylic adhesive to improve the adhesion and moisture and heat resistance of the acrylic adhesive at 150-200°C, but the modified calcium carbonate has poor dispersibility and some agglomerates, which is not conducive to the durability and stability of the acrylic adhesive. (Research on calcium carbonate modification and its application in acrylic structural adhesives [D]. Heilongjiang Academy of Sciences, 2024)

[0014] From the above patents and articles, we can find that nano calcium carbonate is often used as a functional filler for adhesives / acrylate adhesives, which has the effect of improving reinforcement and reducing costs. However, the high surface energy, hydrophilicity, oleophobicity and strong polarity of nano calcium carbonate will lead to poor fluidity of acrylate adhesives during processing and weak bonding with the matrix in acrylate adhesives, which can easily cause interface defects and lead to a decrease in material performance. Summary of the invention

[0015] Aiming at the problems of poor aging resistance and mechanical properties of nano calcium carbonate in the application of acrylic adhesive, the present invention provides a method for preparing nano calcium carbonate special for acrylic adhesive. The method modifies the nano calcium carbonate and fills the prepared secondary modified nano calcium carbonate in the acrylic adhesive, thereby improving the wet heat aging resistance and thixotropy of the acrylic adhesive, and improving the adhesion, durability and stability of the acrylic adhesive. The process is simple and easy to industrialize.

[0016] To achieve the above object, the present invention adopts the following technical solution:

[0017] A method for preparing nano calcium carbonate for acrylic adhesive comprises the following steps:

[0018] S1: diluting lime milk to obtain lime milk slurry, introducing a mixed gas containing carbon dioxide under stirring conditions to perform a carbonation reaction, and when the pH of the reaction system is ≤7.5, stopping the aeration, aging for 1 to 2 hours, and obtaining a calcium carbonate suspension;

[0019] S2: Surface modification of nano calcium carbonate suspension using a mixture of polyoxyethylene glyceryl triricinoleate, nonylphenol polyoxyethylene ether sulfate and sodium stearate;

[0020] S3: After ultrasonic treatment for 30 minutes, propyl triethoxysilane was added to the nano-calcium carbonate suspension after the primary modification to perform secondary surface modification treatment;

[0021] S4: The modified nano calcium carbonate slurry is filtered, dried, crushed and sieved to obtain nano calcium carbonate for improving the moisture and heat aging resistance of acrylic adhesive.

[0022] Preferably, in step S1, the specific gravity of the lime milk slurry is 1.060-1.075.

[0023] Preferably, in step S1, the carbon dioxide concentration is 15-30% and the flow rate is 1-4 m 3 / h.

[0024] Preferably, in step S2, the amount of the surfactant compound is 3-4.6% of the dry weight of calcium carbonate, wherein the amount of sodium stearate added is 2.3-3.5% of the dry weight of calcium carbonate, the amount of polyoxyethylene glycerol triricinoleate added is 0.4-0.6% of the dry weight of calcium carbonate, and the amount of nonylphenol polyoxyethylene ether sulfate added is 0.3-0.5% of the dry weight of calcium carbonate.

[0025] Preferably, in step S2, the surface treatment is carried out at a stirring speed of 2500 to 3000 r / min, a temperature of 80 to 95° C., and a modification time of 30 to 50 min.

[0026] Preferably, in step S3, the amount of isocyanatepropyltriethoxysilane added is 0.05-0.2% of the dry weight of calcium carbonate.

[0027] Preferably, in step S3, the surface modification conditions are: a stirring speed of 2800 to 3000 r / min, a temperature of ≥90° C., and a modification time of 20 to 30 min.

[0028] Preferably, in step S4, the drying temperature is 105-120° C. and the drying time is 5-10 hours.

[0029] Preferably, in step S4, the sieving mesh number is 150-200 meshes.

[0030] Compared with the existing technology, the present invention has the following technical advantages:

[0031] 1. The core highlight of the present invention in the first surface modification treatment is that it creatively uses a small amount of highly efficient polyoxyethylene triricinoleate, nonylphenol polyoxyethylene ether sulfate and sodium stearate for compounding. Sodium stearate, which has both a long carbon chain lipophilic end and a carboxyl hydrophilic end, is a commonly used surface treatment agent for nano calcium carbonate, which can greatly improve its lipophilicity, and its suspension is alkaline and cost-effective; polyoxyethylene triricinoleate is a polyoxyethylene fatty acid ester nonionic emulsifier with good emulsifying properties, which can emulsify sodium stearate evenly in water, avoiding the agglomeration phenomenon that may occur in traditional methods. This step not only optimizes the dispersion state of sodium stearate, but also lays the foundation for the subsequent uniform coating of nano calcium carbonate; and nonylphenol polyoxyethylene ether sulfate is obtained by sulfation of a widely used nonionic surfactant nonylphenol polyoxyethylene ether, which not only has a strong stabilizing effect brought by the epoxy group, but also introduces anionic characteristics through the sulfate group, enhancing its applicability in a variety of environments. This dual feature enables nonylphenol polyoxyethylene ether sulfate to form a strong synergistic effect with polyoxyethylene glyceryl triricinoleate, jointly promoting the formation of a uniform and dense coating layer of sodium stearate on the surface of nano-calcium carbonate. This coating layer effectively reduces the interaction between nano-calcium carbonate particles, prevents the occurrence of agglomeration, greatly improves the dispersion performance of modified nano-calcium carbonate in the acrylic adhesive system, and is conducive to the full combination of nano-calcium carbonate and the matrix.

[0032] 2. The present invention innovatively introduces isocyanatepropyltriethoxysilane (IPTES) in the secondary surface modification technology of nano-calcium carbonate. As a type of low-molecular organic silicon compound with a special structure, the isocyanate group of IPTES has high reactivity and strong bonding ability, which effectively promotes its close bonding with the surface of nano-calcium carbonate, forming a strong and durable interface layer; while the siloxane group has high temperature resistance and chemical corrosion resistance, which greatly improves the stability of nano-calcium carbonate in extreme environments and improves the adhesion and durability of acrylic adhesives.

[0033] 3. The modified nano calcium carbonate prepared by the unique modification method of the present invention enhances the moisture and heat aging resistance of the adhesive when filled into the acrylic adhesive, and can maintain its excellent physical and chemical stability even in a high temperature and high humidity environment for a long time, effectively extending the service life of the adhesive; at the same time, this modification also greatly improves the adhesion and durability of the acrylic adhesive, enabling it to more firmly bond to the surfaces of various materials and maintain stable performance under various complex stress conditions; the entire modification process is simple and easy to industrialize. DETAILED DESCRIPTION

[0034] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0035] In an embodiment of the present invention, a method for preparing nano calcium carbonate for acrylic adhesive comprises the following steps:

[0036] S1: diluting lime milk to obtain lime milk slurry, introducing a mixed gas containing carbon dioxide under stirring conditions to perform a carbonation reaction, and when the pH of the reaction system is ≤7.5, stopping the aeration, aging for 1 to 2 hours, and obtaining a calcium carbonate suspension;

[0037] S2: Surface modification of nano calcium carbonate suspension using a mixture of polyoxyethylene glyceryl triricinoleate, nonylphenol polyoxyethylene ether sulfate and sodium stearate;

[0038] S3: After ultrasonic treatment for 30 minutes, propyl triethoxysilane was added to the nano-calcium carbonate suspension after the primary modification to perform secondary surface modification treatment;

[0039] S4: The modified nano calcium carbonate slurry is filtered, dried, crushed and sieved to obtain nano calcium carbonate for improving the moisture and heat aging resistance of acrylic adhesive.

[0040] In step S1, the specific gravity of the lime milk slurry is 1.060-1.075.

[0041] In step S1, the carbon dioxide concentration is 15-30% and the flow rate is 1-4 m 3 / h.

[0042] In step S2, the amount of the surfactant compound is 3-4.6% of the dry weight of calcium carbonate, wherein the amount of sodium stearate added is 2.3-3.5% of the dry weight of calcium carbonate, the amount of polyoxyethylene glycerol triricinoleate added is 0.4-0.6% of the dry weight of calcium carbonate, and the amount of nonylphenol polyoxyethylene ether sulfate added is 0.3-0.5% of the dry weight of calcium carbonate.

[0043] In step S2, the surface treatment is carried out at a stirring speed of 2500 to 3000 r / min, a temperature of 80 to 95°C, and a modification time of 30 to 50 min.

[0044] In step S3, the amount of isocyanatepropyltriethoxysilane added is 0.05-0.2% of the dry weight of calcium carbonate.

[0045] In step S3, the surface modification conditions are: a stirring speed of 2800 to 3000 r / min, a temperature of ≥90° C., and a modification time of 20 to 30 min.

[0046] In step S4, the drying temperature is 105-120° C. and the time is 5-10 hours.

[0047] In step S4, the sieving mesh number is 150-200 meshes.

[0048] Technical principle of the present invention:

[0049] 1. Specific role and synergistic effect of raw materials

[0050] (1) Lime milk and carbon dioxide: Lime milk (calcium hydroxide suspension) is used as the starting material, and a raw slurry with an appropriate specific gravity (1.060-1.075) is obtained by dilution. This step ensures the smooth progress of the subsequent reaction. Subsequently, a mixed gas containing carbon dioxide (concentration 15-30%, flow rate 1-4m 3 / h), triggering the carbonation reaction to generate calcium carbonate. The concentration and flow of carbon dioxide are precisely controlled to form uniform and fine calcium carbonate grains, laying a good foundation for subsequent modification. Carbonation is stopped when pH ≤ 7.5 to ensure that the reaction is sufficient and not excessive, followed by aging for 1 to 2 hours to promote the improvement of the crystal structure and reduce particle agglomeration.

[0051] (2) Surfactant compound: In step S2, the compound of polyoxyethylene triricinoleate, nonylphenol polyoxyethylene ether sulfate and sodium stearate each plays a unique role in surface modification. Sodium stearate, as the main hydrophobic modifier, significantly improves the dispersibility and compatibility of nano-calcium carbonate with organic matter; polyoxyethylene triricinoleate, due to the hydrophilic groups and hydrophobic segments in its molecular structure, enhances the interfacial bonding between calcium carbonate particles and the polymer matrix; nonylphenol polyoxyethylene ether sulfate acts as a dispersant to further refine the particles and prevent agglomeration. The synergistic effect of the three not only improves the dispersibility and stability of nano-calcium carbonate, but also enhances its dispersion uniformity and compatibility in acrylic adhesives, thereby improving the adhesive's resistance to moisture and heat aging.

[0052] (3) Isocyanate propyl triethoxysilane: Isocyanate propyl triethoxysilane introduced in step S3, as a secondary surface modifier, can form a strong organic silicon layer on the surface of calcium carbonate particles due to its unique silane coupling properties. The formed organic silicon layer can enhance the chemical bonding force between nano calcium carbonate and acrylate matrix, thereby improving the overall performance of the entire adhesive system.

[0053] 2. Importance of raw material dosage and process parameters

[0054] The amount of surfactant compound must be strictly controlled within the range of 3-4.6% of the dry weight of calcium carbonate. Too much may increase the viscosity of the system, which is not conducive to subsequent processing; too little will result in poor modification effect. The specific proportions of each component (such as 2.3-3.5% sodium stearate, 0.4-0.6% polyoxyethylene glyceryl triricinoleate, 0.3-0.5% nonylphenol polyoxyethylene ether sulfate) are carefully designed to achieve the best synergistic effect.

[0055] The precise control of process parameters such as stirring speed, temperature and modification time ensures the uniformity and effectiveness of the modification process. In the present invention, the high stirring speed (2500-3000 r / min) promotes the uniform distribution of the surfactant on the surface of the calcium carbonate particles; the appropriate temperature (80-95°C) accelerates the modification reaction; and the precise control of the modification time (30-50 min) ensures that the modification reaction is fully carried out, avoiding particle damage caused by too long or incomplete modification caused by too short a time.

[0056] 3. Necessity and technical effect of optimizing process parameters

[0057] Optimizing process parameters is not only the key to improving product performance, but also an important way to achieve large-scale production and reduce costs. Through repeated experiments and adjustments, in step S3, the stirring speed is fine-tuned to 2800-3000r / min, the temperature is maintained at ≥90°C, and the modification time is controlled to 20-30min, which can significantly improve the interfacial bonding strength between nano-calcium carbonate and acrylic adhesives and further extend the service life of the adhesive. In addition, precise control of drying temperature and time (105-120°C, 5-10h) ensures that nano-calcium carbonate removes residual moisture and volatile substances while maintaining its excellent performance, thereby improving product stability.

[0058] In order to make the disclosure of the present invention more complete, it is described below through more specific embodiments.

[0059] Example 1

[0060] A method for preparing nano calcium carbonate for acrylic adhesive comprises the following steps:

[0061] S1: Dilute the lime milk to obtain lime milk slurry with a specific gravity of 1.068, and introduce carbon dioxide with a concentration of 20% and a flow rate of 2.5m 3 / h of mixed gas for carbonation reaction, when the pH of the reaction system is 7.5, stop aeration, age for 1h, and obtain nano calcium carbonate suspension;

[0062] S2: heating the nano calcium carbonate suspension to 90° C. and maintaining this temperature, starting stirring at a stirring speed of 2800 r / min, then adding 2.8% of sodium stearate by dry weight of calcium carbonate, 0.6% of polyoxyethylene glycerol triricinoleate by dry weight of calcium carbonate and 0.3% of nonylphenol polyoxyethylene ether sulfate by dry weight of calcium carbonate, and stirring for 40 minutes for surface modification treatment;

[0063] S3: heating the nano suspension after ultrasonic dispersion for 30 minutes to 95°C and maintaining this temperature, starting stirring at a stirring speed of 3000r / min, then adding 0.05% of triethoxypropyl isocyanate silane based on the dry weight of calcium carbonate, stirring for 20 minutes for secondary surface modification;

[0064] S4: The nano calcium carbonate suspension after secondary surface modification is filtered, dried at 105° C. for 10 h, crushed, and sieved through 150 meshes to obtain nano calcium carbonate for acrylic adhesive.

[0065] Example 2

[0066] A method for preparing nano calcium carbonate for acrylic adhesive comprises the following steps:

[0067] S1: Dilute the lime milk to obtain lime milk slurry with a specific gravity of 1.070, and introduce carbon dioxide with a concentration of 18% and a flow rate of 2.0 m 3 / h of mixed gas for carbonation reaction, when the pH of the reaction system is 7.4, stop aeration, age for 1.5h, and obtain nano calcium carbonate suspension;

[0068] S2: heating the nano calcium carbonate suspension to 95° C. and maintaining this temperature, starting stirring at a stirring speed of 2800 r / min, then adding 3.0% sodium stearate by dry weight of calcium carbonate, 0.5% polyoxyethylene glycerol triricinoleate by dry weight of calcium carbonate and 0.4% nonylphenol polyoxyethylene ether sulfate by dry weight of calcium carbonate, and stirring for 40 minutes for surface modification treatment;

[0069] S3: heating the nano suspension after ultrasonic dispersion for 30 minutes to 95°C and maintaining this temperature, starting stirring at a stirring speed of 2800r / min, then adding 0.06% of triethoxypropyl isocyanate silane based on the dry weight of calcium carbonate, stirring for 25 minutes for secondary surface modification;

[0070] S4: The nano calcium carbonate suspension after secondary surface modification is filtered, dried at 110° C. for 8 h, crushed, and sieved through 180 meshes to obtain nano calcium carbonate for acrylic adhesive.

[0071] Example 3

[0072] A method for preparing nano calcium carbonate for acrylic adhesive comprises the following steps:

[0073] S1: Dilute the lime milk to obtain lime milk slurry with a specific gravity of 1.073, and introduce carbon dioxide with a concentration of 28% and a flow rate of 3.5m 3 / h of mixed gas for carbonation reaction, when the pH of the reaction system is 7.3, stop aeration, age for 2h, and obtain nano calcium carbonate suspension;

[0074] S2: heating the nano calcium carbonate suspension to 85° C. and maintaining this temperature, starting stirring at a stirring speed of 2800 r / min, then adding 3.5% of sodium stearate by dry weight of calcium carbonate, 0.6% of polyoxyethylene glycerol triricinoleate by dry weight of calcium carbonate, and 0.5% of nonylphenol polyoxyethylene ether sulfate by dry weight of calcium carbonate, and stirring for 50 minutes for surface modification treatment;

[0075] S3: heating the nano suspension after ultrasonic dispersion for 30 minutes to 90°C and maintaining this temperature, starting stirring at a stirring speed of 3000r / min, then adding 0.08% of isocyanatepropyltriethoxysilane based on the dry weight of calcium carbonate, stirring for 30 minutes for secondary surface modification;

[0076] S4: The nano calcium carbonate suspension after secondary surface modification is filtered, dried at 115° C. for 6 hours, crushed, and sieved through 180 meshes to obtain nano calcium carbonate for acrylic adhesive.

[0077] Example 4

[0078] A method for preparing nano calcium carbonate for acrylic adhesive comprises the following steps:

[0079] S1: Dilute the lime milk to obtain lime milk slurry with a specific gravity of 1.060, and introduce carbon dioxide with a concentration of 15% and a flow rate of 2m 3 / h of mixed gas for carbonation reaction, when the pH of the reaction system is 7.4, stop aeration, age for 1h, and obtain nano calcium carbonate suspension;

[0080] S2: heating the nano calcium carbonate suspension to 90° C. and maintaining this temperature, starting stirring at a stirring speed of 2500 r / min, then adding 2.3% of sodium stearate by dry weight of calcium carbonate, 0.4% of polyoxyethylene glycerol triricinoleate by dry weight of calcium carbonate and 0.3% of nonylphenol polyoxyethylene ether sulfate by dry weight of calcium carbonate, and stirring for 45 minutes for surface modification treatment;

[0081] S3: heating the nano suspension after ultrasonic dispersion for 30 minutes to 93°C and maintaining this temperature, starting stirring at a stirring speed of 2800 r / min, then adding 0.07% of isocyanatepropyltriethoxysilane based on the dry weight of calcium carbonate, stirring for 25 minutes for secondary surface modification;

[0082] S4: The nano calcium carbonate suspension after secondary surface modification is filtered, dried at 120° C. for 5 h, crushed, and sieved through 200 meshes to obtain nano calcium carbonate for acrylic adhesive.

[0083] Comparative Example 1

[0084] A preparation method of a nano calcium carbonate product comprises the following steps:

[0085] S1: Dilute the lime milk to obtain lime milk slurry with a specific gravity of 1.070, and introduce carbon dioxide with a concentration of 28% and a flow rate of 3.5m 3 / h of mixed gas for carbonation reaction, when the pH of the reaction system is 7.5, stop aeration, age for 2h, and obtain nano calcium carbonate suspension;

[0086] S2: The nano calcium carbonate suspension obtained in S1 is filtered, dried at 120° C. for 5 h, crushed, and passed through a 150-mesh sieve to obtain a nano calcium carbonate product.

[0087] Comparative Example 2

[0088] A preparation method of a nano calcium carbonate product comprises the following steps:

[0089] S1: Dilute the lime milk to obtain lime milk slurry with a specific gravity of 1.070, and introduce carbon dioxide with a concentration of 28% and a flow rate of 3.5m 3 / h of mixed gas for carbonation reaction, when the pH of the reaction system is 7.5, stop aeration, age for 2h, and obtain nano calcium carbonate suspension;

[0090] S2: heating the nano calcium carbonate suspension to 95°C and maintaining this temperature, starting stirring at a stirring speed of 3000 r / min, then adding 3.5% sodium stearate by dry weight of calcium carbonate, stirring for 40 minutes for surface modification;

[0091] S3: The nano calcium carbonate suspension obtained in S2 is filtered, dried at 120° C. for 5 h, crushed, and passed through a 150-mesh sieve to obtain a nano calcium carbonate product.

[0092] Comparative Example 3

[0093] A preparation method of a nano calcium carbonate product comprises the following steps:

[0094] S1: Dilute the lime milk to obtain lime milk slurry with a specific gravity of 1.070, and introduce carbon dioxide with a concentration of 28% and a flow rate of 3.5m 3 / h of mixed gas for carbonation reaction, when the pH of the reaction system is 7.5, stop aeration, age for 2h, and obtain nano calcium carbonate suspension;

[0095] S2: heating the nano calcium carbonate suspension to 95°C and maintaining this temperature, starting stirring at a stirring speed of 3000 r / min, then adding 3.5% polyoxyethylene glycerol triricinoleate based on the dry weight of calcium carbonate, stirring for 40 minutes for surface modification treatment;

[0096] S3: The nano calcium carbonate suspension obtained in S2 is filtered, dried at 120° C. for 5 h, crushed, and passed through a 150-mesh sieve to obtain a nano calcium carbonate product.

[0097] Comparative Example 4

[0098] A preparation method of a nano calcium carbonate product comprises the following steps:

[0099] S1: Dilute the lime milk to obtain lime milk slurry with a specific gravity of 1.070, and introduce carbon dioxide with a concentration of 28% and a flow rate of 3.5m 3 / h of mixed gas for carbonation reaction, when the pH of the reaction system is 7.5, stop aeration, age for 2h, and obtain nano calcium carbonate suspension;

[0100] S2: heating the nano calcium carbonate suspension to 95°C and maintaining this temperature, starting stirring at a stirring speed of 3000 r / min, then adding 3.5% of nonylphenol polyoxyethylene ether sulfate by dry weight of calcium carbonate, stirring for 40 minutes for surface modification treatment;

[0101] S3: The nano calcium carbonate suspension obtained in S2 is filtered, dried at 120° C. for 5 h, crushed, and passed through a 150-mesh sieve to obtain a nano calcium carbonate product.

[0102] Comparative Example 5

[0103] A preparation method of a nano calcium carbonate product comprises the following steps:

[0104] S1: Dilute the lime milk to obtain lime milk slurry with a specific gravity of 1.070, and introduce carbon dioxide with a concentration of 28% and a flow rate of 3.5m 3 / h of mixed gas for carbonation reaction, when the pH of the reaction system is 7.5, stop aeration, age for 2h, and obtain nano calcium carbonate suspension;

[0105] S2: heating the nano calcium carbonate suspension to 95° C. and maintaining this temperature, starting stirring at a stirring speed of 3000 r / min, then adding 0.2% of nonylphenol polyoxyethylene ether sulfate by dry weight of calcium carbonate, stirring for 40 minutes for surface modification treatment;

[0106] S3: The nano calcium carbonate suspension obtained in S2 is filtered, dried at 120° C. for 5 h, crushed, and passed through a 150-mesh sieve to obtain a nano calcium carbonate product.

[0107] Performance test experiment:

[0108] The nano calcium carbonate obtained in the above-mentioned embodiments 1 to 4 and comparative examples 1 to 5 was used to prepare acrylic adhesives according to the formula in Table 1 and the conventional method, and the surface drying time, bonding strength, tensile strength, shear strength, Shore hardness, elongation at break, and moisture and heat resistance were tested with reference to GB / T13477.3-2017, GB / T11211-2009, GB / T528-2009, GB / T7124-2008, GB / T531.1-2008, and JG / T465-2014, wherein the moisture and heat resistance was tested under the conditions of 120°C and 100% relative humidity for 24 hours and 48 hours. The test results of the embodiments and comparative examples are shown in Table 2.

[0109] Table 1 Acrylic adhesive formulation

[0110]

[0111]

[0112] Table 2 Performance test results of nano calcium carbonate obtained in the embodiments and comparative examples

[0113]

[0114] From the test results in Table 2, it can be seen that the nano calcium carbonate surface treated by the methods of Examples 1 to 4 of the present invention is filled in the acrylic adhesive, and its bonding strength, tensile strength, shear strength, Shore hardness, and elongation at break are significantly greater than those of Comparative Examples 1 to 5. After the 24h and 48h wet heat resistance tests of the acrylic adhesives of Examples 1 to 4, the bonding strength, tensile strength, and elongation at break of the Examples can be maintained at more than 80%, while those of Comparative Examples 1 to 5 are less than 78%; this shows that the weather resistance of each Example is significantly superior to that of the Comparative Example.

[0115] When further exploring the effects of different surface treatment agents on the performance of acrylic adhesives, the significant changes of Comparative Examples 2 to 5 compared with Comparative Example 1 were analyzed. In Comparative Example 2, sodium stearate was introduced alone as a surface treatment agent for nano-calcium carbonate to reduce the surface energy of nano-calcium carbonate, reduce the resistance and gaps between interfaces, and promote the dispersion and infiltration of nano-calcium carbonate particles in the acrylic matrix. Compared with the unmodified nano-calcium carbonate filling system in Comparative Example 1, not only the tensile strength of the adhesive was enhanced, but also the shear strength and elongation at break were significantly improved.

[0116] In contrast, when polyoxyethylene glycerol triricinoleate, nonylphenol polyoxyethylene ether sulfate and isocyanate propyl triethoxysilane were used as separate surface treatment agents in Comparative Examples 3, 4 and 5, although the dispersibility and compatibility of nano-calcium carbonate with the matrix were improved to a certain extent, the effect did not reach the significant level of Comparative Example 2. This may be because the mechanism of action or efficiency of these treatment agents in reducing surface energy and promoting interface bonding is not as direct and effective as sodium stearate, and they fail to fully cover the surface of nano-calcium carbonate particles and form a sufficient protective layer to prevent agglomeration between particles, or their solubility and dispersibility in the matrix are not ideal, resulting in limited improvement in interface bonding strength.

[0117] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for preparing nano calcium carbonate for acrylic adhesive, characterized in that: The following steps are involved: S1: diluting lime milk to obtain lime milk slurry, introducing a mixed gas containing carbon dioxide into the slurry under stirring conditions to perform a carbonation reaction, stopping the aeration when the reaction is completed, and aging the slurry to obtain a calcium carbonate suspension; S2: Surface modification of nano calcium carbonate suspension using a mixture of polyoxyethylene glyceryl triricinoleate, nonylphenol polyoxyethylene ether sulfate and sodium stearate; S3: adding isocyanatepropyltriethoxysilane to the nano-calcium carbonate suspension after ultrasonic treatment for secondary surface modification; S4: The modified nano calcium carbonate slurry is filtered, dried, crushed and sieved to obtain nano calcium carbonate for improving the moisture and heat aging resistance of acrylic adhesive.

2. The method for preparing nano calcium carbonate for acrylic adhesive according to claim 1, characterized in that: In step S1, the specific gravity of the lime milk slurry is 1.060-1.

075.

3. The method for preparing nano calcium carbonate for acrylic adhesive according to claim 1, characterized in that: The carbon dioxide concentration in step S1 is 15-30% and the flow rate is 1-4m 3 / h.

4. The method for preparing nano calcium carbonate for acrylic adhesive according to claim 1, characterized in that: In step S2, the amount of the surfactant compound is 3-4.6% of the dry weight of calcium carbonate.

5. The method for preparing nano calcium carbonate for acrylic adhesive according to claim 4, characterized in that: The added amount of sodium stearate in the compound surfactant is 2.3-3.5%, the added amount of polyoxyethylene glycerol triricinoleate is 0.4-0.6%, and the added amount of nonylphenol polyoxyethylene ether sulfate is 0.3-0.5%.

6. The method for preparing nano calcium carbonate for acrylic adhesive according to claim 1, characterized in that: In step S2, the surface treatment is carried out at a stirring speed of 2500-3000 r / min and a temperature of 80-95° C. for 30-50 min.

7. The method for preparing nano calcium carbonate for acrylic adhesive according to claim 1, characterized in that: In step S3, the amount of isocyanatepropyltriethoxysilane added is 0.05-0.2% of the dry weight of calcium carbonate.

8. The method for preparing nano calcium carbonate for acrylic adhesive according to claim 1, characterized in that: In step S3, the surface modification conditions are: stirring speed of 2800-3000 r / min, temperature ≥90°C, and modification for 20-30 min.

9. The method for preparing nano calcium carbonate for acrylic adhesive according to claim 1, characterized in that: In step S4, the drying temperature is 105-120° C., and the drying time is 5-10 hours; and the sieving mesh size is 150-200 meshes.

10. Nano calcium carbonate specially used for acrylic adhesive prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-weatherability structural adhesive and preparation method thereof

    CN103305131B

  • Surface treatment method for nano calcium carbonate special for photovoltaic adhesive

    CN105778568A

  • Ageing resistance composite calcium carbonate and preparation method thereof

    CN106243780A

  • Acrylate adhesive for cementing skirting line ofhigh-speed train

    CN106752984A

  • Structural adhesive for automobile and preparation method of structural adhesive

    CN113025215A